Understanding ecosystem responses to recurrent marine heatwaves - Emily Lester; Stanley Mastrantonis; Sharyn M. Hickey; Anna Lafratta; Jessica A. Benthuysen; Eben Afrifa-Yamoah; Arani Chandrapavan; Martial Depczynski; Richard D. Evans; David V. Fairclough; Christopher J. Fulton; Marthe Monique Gagnon; et al. (Biological Conservation, 2026)

Towards ecosystem-based fisheries management in an economically constrained context: Giving more consideration to the ecosystem approach to fisheries management - Arnaud Grüss; Samik Datta; Vidette McGregor-Tiatia; Steven J. Holmes; Jean P. Davis; Elizabeth A. Fulton; Éva E. Plagányi; Keith Sainsbury; Paul J. Dolder; Mahdi Parsa; Jeffrey M. Dambacher; Raymond Czaja; et al. (Fisheries Research, 2026)

Exploring trip preference heterogeneity in away-from-home birdwatchers using a discrete choice experiment - Katherine A. Sainsbury; Howard W. Harshaw; Nicholas W. Cole; Mark P. Vrtiska; David C. Fulton; Andrew H. Raedeke; Ashley A. Dayer; Jennie N. Duberstein; Rudy M. Schuster (Journal of Outdoor Recreation and Tourism, 2026)

Impacts of Diverse Stakeholder Participation on Fisheries Management - Sangeeta Mangubhai; S. L. Smith; Z. Davis; N. Koedyker; J. Augustyn; D. Durholtz; S. Fulton; Harlisa; M. T. Hidayat; L. Hiriart-Bertrand; M. Khazali; E. Litsinger; et al. (Coastal Management, 2026)

Regional drivers of soybean farmers’ yield, seed protein, and oil concentration - Valentina M. Pereyra; Carlos Hernandez; Trevor Hefley; Ajay Sharda; P.V. Vara Prasad; Laila Puntel; Guillermo R. Balboa; David Moseley; J. Trenton Irby; Eros Francisco; André F.B. Reis; Aaron Prestholt; et al. (Field Crops Research, 2026)

Paleoenvironmental and diagenetic effects on porphyrin distributions in the End-Devonian Exshaw Formation, Western Canada - Sanjukta Dhar; James M. Fulton (Organic Geochemistry, 2025)

The infrastructure cost for depot charging of battery electric trucks - Guihua Wang; Marshall R. Miller; Lewis M. Fulton (The Electricity Journal, 2025)

Cascading tipping points of Antarctica and the Southern Ocean - Ida Kubiszewski; Vanessa M. Adams; Rachel Baird; Anne Boothroyd; Robert Costanza; Darla Hatton MacDonald; Glenn Finau; Elizabeth A. Fulton; Catherine K. King; Matt A. King; Delphine Lannuzel; Elizabeth Leane; et al. (Ambio, 2025)
Antarctica and the Southern Ocean are key elements in the physical and biological Earth system. Human-induced climate change, and other human activities in the region, are leading to several potential interacting tipping points with major and irreversible consequences. Here, we examine eight potential physical, biological, chemical, and social Antarctic tipping points. These include ice sheets, ocean acidification, ocean circulation, species redistribution, invasive species, permafrost melting, local pollution, and the Antarctic Treaty System. We discuss the nature of each potential tipping point, its control variables, thresholds, timescales, and impacts, and focus on the potential for cumulative and cascading effects as a result of their interactions. The analysis provides substantial evidence of the need for more concerted and rapid action to limit climate change and to minimise the impacts of local human activities to avoid these cascading tipping points.

Predicting and assessing the impacts of COVID-19 disruption on marine science and sectors in Australia - Alistair J. Hobday; Vicki M. Walters; Robert L. Stephenson; Shane Baylis; Cindy Bessey; Fabio Boschetti; Catherine Bulman; Stephanie Contardo; Jeffrey M. Dambacher; Jemery Day; Natalie A. Dowling; Piers Dunstan; et al. (Reviews in Fish Biology and Fisheries, 2025)
By March 2020 coronavirus disease 2019 (COVID-19) was anticipated to present a major challenge to the work undertaken by scientists. This pandemic could be considered just one of the shocks that human society has had and will be likely to confront again in the future. As strategic thinking about the future can assist performance and planning of scientific research in the face of change, the pandemic presented an opportunity to evaluate the performance of marine researchers in prediction of future outcomes. In March 2020, two groups of researchers predicted outcomes for the Australian marine research sector, and then evaluated these predictions after 18 months. The self-assessed coping ability of a group experienced in ‘futures studies’ was not higher than the less-experienced group, suggesting that scientists in general may be well placed to cope with shocks. A range of changes to scientific endeavours (e.g., travel, fieldwork) and to marine sectors (e.g., fisheries, biodiversity) were predicted over the first 12–18 months of COVID-19 disruption. The predicted direction of change was generally correct (56%) or neutral (25%) for predictions related to the scientific endeavour, and correct (73%) or mixed (9%) for predictions related to sectors that are the focus of marine research. The success of this foresighting experiment suggests that the collective wisdom of scientists can be used by their organisations to consider the impact of shocks and disruptions and to better prepare for and cope with shocks. Graphical abstract Word cloud analysis of free text responses to questions about expected impact of COVID-19 on the activities associated with marine science

On-farm experimentation: assessing the effect of combine ground speed on grain yield monitor data estimates - A. A. Gauci; A. Lindsey; S. A. Shearer; D. Barker; E. M. Hawkins; John P. Fulton (Precision Agriculture, 2025)

Small-scale fisheries in ecologically sensitive areas in Latin America and the Caribbean: Do marine protected areas benefit fisheries governance? - Ana Cinti; Luisa Ramirez; Mauricio Castrejón; Jaime A. Aburto; Luciana Loto; Stuart Fulton; Mario Rueda; Alexandre Schiavetti; Francisco J. Fernández-Rivera Melo; Manuel Bravo; Daniela Trigueirinho Alarcon; Valéria Penchel Araújo; et al. (Ambio, 2025)
Many small-scale fisheries (SSFs) in Latin America and the Caribbean (LAC) operate in ecologically sensitive areas, where balancing conservation and resource use is challenging. 'Multiple-use' marine protected areas (MPAs) have been implemented to accommodate SSFs (among other uses) within areas designated for conservation, creating opportunities and challenges for SSF governance. We analyzed eleven case studies from LAC to explore: (1) how different MPA institutional designs affect key aspects of SSF governance and (2) the links between these effects and the type of initiative that promoted MPA establishment (origin). Results indicate that the existence of an MPA benefited SSF governance in many ways, with more pronounced positive effects in MPAs with mixed to bottom-up origin supported by well-organized fishing groups. In addition, the presence of supportive MPA authorities that leveraged local capacities and initiatives and adopted flexible and collaborative governance systems made a difference in several cases. Lessons for integrating MPA and SSF governance are drawn.

Inshore coral reef sediment and turf dynamics unaffected by canopy-forming macroalgae - Stella E. Fulton; Tehya Hines; Cathie A. Page; Ian M. McLeod; James Whinney; Scott F. Heron; David G. Bourne; Hillary A. Smith (Marine Pollution Bulletin, 2024)

Social influence modelling demonstrates that strategic communication and depoliticization reduces conflict in aquaculture - C.M. Condie; E.A. Fulton; K.A. Alexander; J. Vince; M. Haward; S.A. Condie (Marine Policy, 2024)

Cost–benefit analysis of ecosystem modeling to support fisheries management - Matthew H. Holden; Eva E. Plagányi; Elizabeth A. Fulton; Alexander B. Campbell; Rachel Janes; Robyn A. Lovett; Montana Wickens; Matthew P. Adams; Larissa Lubiana Botelho; Catherine M. Dichmont; Philip Erm; Kate J. Helmstedt; et al. (Journal of Fish Biology, 2024)
Mathematical and statistical models underlie many of the world's most important fisheries management decisions. Since the 19th century, difficulty calibrating and fitting such models has been used to justify the selection of simple, stationary, single‐species models to aid tactical fisheries management decisions. Whereas these justifications are reasonable, it is imperative that we quantify the value of different levels of model complexity for supporting fisheries management, especially given a changing climate, where old methodologies may no longer perform as well as in the past. Here we argue that cost‐benefit analysis is an ideal lens to assess the value of model complexity in fisheries management. While some studies have reported the benefits of model complexity in fisheries, modeling costs are rarely considered. In the absence of cost data in the literature, we report, as a starting point, relative costs of single‐species stock assessment and marine ecosystem models from two Australian organizations. We found that costs varied by two orders of magnitude, and that ecosystem model costs increased with model complexity. Using these costs, we walk through a hypothetical example of cost‐benefit analysis. The demonstration is intended to catalyze the reporting of modeling costs and benefits.

Precision of grain yield monitors for use in on-farm research strip trials - A. A. Gauci; J. P. Fulton; A. Lindsey; S. A. Shearer; D. Barker; E. M. Hawkins (Precision Agriculture, 2024)
On-farm research (OFR) has become popular as a result of precision agriculture technology simplifying the process and farm software capabilities to summarize results collected through the technology. Different OFR designs exists with strip-trials being a simple approach to evaluate different treatments. Common in OFR is the use of yield monitors to collect crop performance data since yield represents a primary response variable in these type studies. The objective was to investigate the ability of grain yield monitoring technologies to accurately inform strip trials when frequent yield variability exists within an experimental unit. A combination of six sub-plot treatment resolutions (TR) that differed in length of imposed yield variation (7.6, 15.2, 30.5, 61.0, 121.9, and 243.8 m) were harvested at combine ground speeds of 3.2, 6.4, 7.2, and 8.1 kph, depending on study site (three study sites total). Intentional yield differences in maize ( Zea mays L. ) were created for each sub-plot by alternating the amount nitrogen (N) applied: 0 or 202 kg N/ha. Yield was measured by four commercially available yield monitoring (YM) technologies and a weigh wagon. Comparisons were made between the accumulated mass of the YM technology and weigh wagon through percent differences along with testing the significance of the plotted relationship between YM and weigh wagon. Results indicated that yield monitoring technology can be used to evaluate strip trial performance regardless of yield frequency and variability (error < 3%) within an experimental unit when operating within the calibrated range of the mass flow sensor. Operating outside of the calibrated range of the mass flow sensor resulted in > 15% error in estimating accumulated weight and overestimation of yield by 23%. Finally, no significant differences existed in estimating accumulated weight values between grain yield monitor technologies (all p-values ≥ 0.54).

Perceived constraints to participating in wildlife-related recreation - Nicholas W. Cole; Emily J. Wilkins; Kaylin R. Clements; Rudy M. Schuster; Ashley A. Dayer; H.W. Harshaw; David C. Fulton; Jennifer N. Duberstein; Andrew H. Raedeke (Journal of Outdoor Recreation and Tourism, 2024)

Insights into the environment surrounding the subduction megathrust using teleseismic P-to-S and P-to-P scattered phases - Michael Everett Mann; Geoffrey A. Abers; Patrick M. Fulton (Earth and Planetary Science Letters, 2024)

What waterfowl hunters want: exploring heterogeneity in hunting trip preferences - Katherine A. Sainsbury; Howard W. Harshaw; David C. Fulton; Nicholas W. Cole; Ashley A. Dayer; Jennie N. Duberstein; Andrew H. Raedeke; Rudy M. Schuster; Mark P. Vrtiska (Wetlands, 2024)
Canadian and American waterfowl hunters were surveyed to identify their hunting trip preferences. Respondents were individuals that were now participating or had participated in waterfowl hunting, and most had hunted the majority of the last five years. We identified four latent classes of waterfowl hunters that varied in their preferences for harvest, access effort, length of travel, quantity of waterfowl seen, and the potential for interference/competition. We found a diminishing return associated with the number of waterfowl harvested, and that ‘devoted’ and ‘local’ hunters did not perceive appreciable benefit from harvesting more birds beyond harvesting a single bird. Results highlight the importance of not only considering population size, but also the location of habitat for people and waterfowl. Our results provide waterfowl managers important insights into the heterogeneity of North American waterfowl hunters by highlighting differences in priorities for waterfowl hunting trips. Notably, to address this heterogeneity, managers could consider the balance of objectives, actions and resources designed to satisfy current waterfowl hunters. Managing access to improve the likelihood that hunters will see and have opportunities to harvest some waterfowl has benefit to hunters.

A synthesis of approaches to support integrated assessments of hazards for the emerging Blue Economy - M.P. Turschwell; E.A. Fulton; J. Melbourne-Thomas; M. Lacharité; K.R. Hayes; G. Wood; K. Evans; D. Hatton MacDonald; J. Dambacher; R.H. Bustamante; R. Abbassi; P. Fidelman; et al. (Marine Policy, 2023)

Co-designing a multi-criteria approach to ranking hazards to and from Australia’s emerging offshore blue economy - Mischa P. Turschwell; Christopher J. Brown; Myriam Lacharité; Jess Melbourne-Thomas; Keith R. Hayes; Rodrigo H. Bustamante; Jeffrey M. Dambacher; Karen Evans; Pedro Fidelman; Darla Hatton MacDonald; Ingrid Van Putten; Graham Wood; et al. (Environmental Science & Policy, 2023)

Effects of vertical mixing on the Lake Michigan food web: an application of a linked end-to-end earth system model framework - H. Zhang; D. M. Mason; N. W. Boucher; E. S. Rutherford; D. J. Cannon; J. Kessler; A. Fujisaki-Manome; J. Wang; E. A. Fulton (Ocean Dynamics, 2023)
Physical processes may affect ecosystem structure and function through the accumulation, transport, and dispersal of organic and inorganic materials, nutrients, and organisms; they structure physical habitat and can influence predator–prey interactions and trophic production. In the Laurentian Great Lakes, horizontal currents generally dominate, but little is known about the effects of vertical mixing on lake food webs. We developed a linked earth system model and used it to explore how vertical mixing affects the productivity of Lake Michigan (LM), the world’s fifth-largest lake, whose food web and fisheries have been adversely affected by invasive Dreissena mussels. We hypothesized that higher vertical mixing would result in higher food web biomass by making phosphorus more available to the lower food web, and that filtration by invasive mussels would counter the effects of mixing and decrease food web biomass. Using linked climate, hydrodynamics, and ecosystem models, we projected the response of LM’s food web to scenarios of different levels of vertical mixing, with and without invasive mussels. Biomass of most functional food web groups increased with increases in vertical mixing, with the greatest increases in phytoplankton and zooplankton. Increased biomass was due to the replenishment of nutrients into the euphotic zone, which enhanced growth and biomass of lower trophic levels through bottom-up effects. However, filtration by invasive mussels reduced the positive effects of mixing for most species. Future applications of the linked earth system framework will explore the effects of climate warming and nutrient reduction on fisheries production to inform fisheries managers.

Towards vibrant fish populations and sustainable fisheries that benefit all: learning from the last 30 years to inform the next 30 years - Steven J. Cooke; Elizabeth A. Fulton; Warwick H. H. Sauer; Abigail J. Lynch; Jason S. Link; Aaron A. Koning; Joykrushna Jena; Luiz G. M. Silva; Alison J. King; Rachel Kelly; Matthew Osborne; Julia Nakamura; et al. (Reviews in Fish Biology and Fisheries, 2023)

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Residence times of groundwater along a flow path in the Great Artesian Basin determined by 81Kr, 36Cl and 4He: Implications for palaeo hydrogeology - R. Purtschert; A.J. Love; W. Jiang; Z.-T. Lu; G.-M. Yang; S. Fulton; D. Wohling; P. Shand; W. Aeschbach; L. Bröder; P. Müller; Y. Tosaki (Science of The Total Environment, 2023)

The contribution of macroalgae‐associated fishes to small‐scale tropical reef fisheries - Shaun K. Wilson; Christopher J. Fulton; Nicholas A.J. Graham; Rene A. Abesamis; Charlotte Berkström; Darren J. Coker; Martial Depczynski; Richard D. Evans; Rebecca Fisher; Jordan Goetze; Andrew Hoey; Thomas H. Holmes; et al. (Fish and Fisheries, 2022)
Macroalgae‐dominated reefs are a prominent habitat in tropical seascapes that support a diversity of fishes, including fishery target species. To what extent, then, do macroalgal habitats contribute to small‐scale tropical reef fisheries? To address this question we: (1) Quantified the macroalgae‐associated fish component in catches from 133 small‐scale fisheries, (2) Compared life‐history traits relevant to fishing (e.g. growth, longevity) in macroalgal and coral‐associated fishes, (3) Examined how macroalgae‐associated species can influence catch diversity, trophic level and vulnerability and (4) Explored how tropical fisheries change with the expansion of macroalgal habitats using a case study of fishery‐independent data for Seychelles. Fish that utilised macroalgal habitats comprise 24% of the catch, but very few fished species relied entirely on macroalgal or coral habitats post‐settlement. Macroalgal and coral‐associated fishes had similar life‐history traits, although vulnerability to fishing declined with increasing contribution of macroalgae association to the catch, whilst mean trophic level and diversity peaked when macroalgal‐associated fish accounted for 20%–30% of catches. The Seychelles case study revealed similar total fish biomass on macroalgal and coral reefs, although the biomass of primary target species increased as macroalgae cover expanded. Our findings reinforce that multiple habitat types are needed to support tropical fishery stability and sustainability. Whilst coral habitats have been the focus of tropical fisheries management, we show the potential for macroalgae‐associated fish to support catch size and diversity in ways that reduce vulnerability to overfishing. This is pertinent to seascapes where repeated disturbances are facilitating the replacement of coral reef with macroalgal habitats.

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Food for all: designing sustainable and secure future seafood systems - A. K. Farmery; K. Alexander; K. Anderson; J. L. Blanchard; C. G. Carter; K. Evans; M. Fischer; A. Fleming; S. Frusher; E. A. Fulton; B. Haas; C. K. MacLeod; et al. (Reviews in Fish Biology and Fisheries, 2022)

Deep aspirations: towards a sustainable offshore Blue Economy - Camilla Novaglio; Narissa Bax; Fabio Boschetti; Gholam Reza Emad; Stewart Frusher; Liam Fullbrook; Mark Hemer; Sarah Jennings; Ingrid van Putten; Lucy M. Robinson; Erica Spain; Joanna Vince; et al. (Reviews in Fish Biology and Fisheries, 2022)

Trying to collapse a population for conservation: commercial trade of a marine invasive species by artisanal fishers - Luis Malpica-Cruz; Stuart Fulton; Anastasia Quintana; Jose Alberto Zepeda-Domínguez; Blanca Quiroga-García; Lizbeth Tamayo; Jose Ángel Canto Noh; Isabelle M. Côté (Reviews in Fish Biology and Fisheries, 2021)

Thiomicrorhabdus streamers and sulfur cycling in perennial hypersaline cold springs in the Canadian high Arctic - Elisse Magnuson; Nadia C.S. Mykytczuk; Andre Pellerin; Jacqueline Goordial; Susan M. Twine; Boswell Wing; Simon J. Foote; Kelly Fulton; Lyle G. Whyte (Environmental Microbiology, 2021)
Summary The Gypsum Hill (GH) springs on Axel Heiberg Island in the Canadian high Arctic are host to chemolithoautotrophic, sulfur‐oxidizing streamers that flourish in the high Arctic winter in water temperatures from −1.3 to 7°C with ~8% salinity in a high Arctic winter environment with air temperatures commonly less than −40°C and an average annual air temperature of −15°C. Metagenome sequencing and binning of streamer samples produced a 96% complete Thiomicrorhabdus sp. metagenome‐assembled genome representing a possible new species or subspecies. This is the most cold‐ and salt‐extreme source environment for a Thiomicrorhabdus genome yet described. Metaproteomic and metatranscriptomic analysis attributed nearly all gene expression in the streamers to the Thiomicrorhabdus sp. and suggested that it is active in CO 2 fixation and oxidation of sulfide to elemental sulfur. In situ geochemical and isotopic analyses of the fractionation of multiple sulfur isotopes determined the biogeochemical transformation of sulfur from its source in Carboniferous evaporites to biotic processes occurring in the sediment and streamers. These complementary molecular tools provided a functional link between the geochemical substrates and the collective traits and activity that define the microbial community's interactions within a unique polar saline habitat where Thiomicrorhabdus ‐dominated streamers form and flourish.

Diazotrophs modulate phycobiliproteins and nitrogen stoichiometry differently than other cyanobacteria in response to light and nitrogen availability - Jingyu Wang; Nicole D. Wagner; James M. Fulton; J. Thad Scott (Limnology and Oceanography, 2021)
Harmful algal blooms (HABs) frequently occur in eutrophic water bodies, which are often dominated by either non‐diazotrophic or diazotrophic strains of cyanobacteria. The occurrence of HABs is associated with multiple environmental factors that affect cyanobacterial growth, though adaptations of cyanobacteria to respond to diverse growing conditions are largely unknown. One factor affecting HAB persistence is the ability of cyanobacteria to synthesize and metabolize large biomolecules such as the light harvesting pigments phycobiliproteins that can also act as nitrogen (N) storage. Here, we examined how cyanobacteria varied phycobiliprotein content in response to different light intensity and N availability in two HAB forming species, Microcystis aeruginosa (non‐diazotrophic) and Dolichospermum flos‐aquae (diazotrophic). Our results revealed both HAB forming species responded similarly to light intensity, with decreasing light causing an increased production of phycobiliproteins, although at different rates. However, we observed dissimilar phycobiliprotein responses to varied N availability. In low N conditions, M. aeruginosa degraded phycobiliproteins primarily due to the decreased need for photosynthesis, whereas D. flos‐aquae , increased phycobiliproteins production under N‐limited conditions likely caused by the increased energetic requirements for N 2 ‐fixation. Our results indicate that M. aeruginosa stored as much as 30% of cellular N in phycobiliproteins under high N conditions, while D. flos‐aquae only allocated 5% of the cellular N in phycobiliproteins. This study reveals a fundamental physiological difference between non‐diazotrophic and diazotrophic cyanobacteria, highlighting the critical role of phycobiliproteins on the persistence of cyanobacteria blooms under scenarios with varied light intensity and N availability.

Minnesota landowners’ trust in their department of natural resources, salient values similarity and wildlife value orientations - Larry M. Gigliotti; Lily A. Sweikert; Louis Cornicelli; David C. Fulton (Environment Systems and Decisions, 2020)

The changing sociocultural context of wildlife conservation - Michael J. Manfredo; Tara L. Teel; Andrew W. Don Carlos; Leeann Sullivan; Alan D. Bright; Alia M. Dietsch; Jeremy Bruskotter; David Fulton (Conservation Biology, 2020)
We introduced a multilevel model of value shift to describe the changing social context of wildlife conservation. Our model depicts how cultural‐level processes driven by modernization (e.g., increased wealth, education, and urbanization) affect changes in individual‐level cognition that prompt a shift from domination to mutualism wildlife values. Domination values promote beliefs that wildlife should be used primarily to benefit humans, whereas mutualism values adopt a view that wildlife are part of one's social network and worthy of care and compassion. Such shifts create emergent effects (e.g., new interest groups) and challenges to wildlife management organizations (e.g., increased conflict) and dramatically alter the sociopolitical context of conservation decisions. Although this model is likely applicable to many modernized countries, we tested it with data from a 2017–2018 nationwide survey (mail and email panel) of 43,949 residents in the United States. We conducted hierarchical linear modeling and correlational analysis to examine relationships. Modernization variables had strong state‐level effects on domination and mutualism. Higher levels of education, income, and urbanization were associated with higher percentages of mutualists and lower percentages of traditionalists, who have strong domination values. Values affected attitudes toward wildlife management challenges; for example, states with higher proportions of mutualists were less supportive of lethal control of wolves ( Canis lupus ) and had lower percentages of active hunters, who represent the traditional clientele of state wildlife agencies in the United States. We contend that agencies will need to embrace new strategies to engage and represent a growing segment of the public with mutualism values. Our model merits testing for application in other countries.

Sectoral Futures Are Conditional on Choices of Global and National Scenarios – Australian Marine Examples - Fabio Boschetti; Catherine M. Bulman; Alistair J. Hobday; Elizabeth A. Fulton; Stephanie Contardo; Hector Lozano-Montes; Lucy M. Robinson; Anthony D. M. Smith; Joanna Strzelecki; E. Ingrid van Putten (Frontiers in Marine Science, 2020)

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Analytical and Computational Advances, Opportunities, and Challenges in Marine Organic Biogeochemistry in an Era of “Omics” - Andrew D. Steen; Stephanie Kusch; Hussain A. Abdulla; Nevenka Cakić; Sarah Coffinet; Thorsten Dittmar; James M. Fulton; Valier Galy; Kai-Uwe Hinrichs; Anitra E. Ingalls; Boris P. Koch; Elizabeth Kujawinski; et al. (Frontiers in Marine Science, 2020)

Macroalgal meadow habitats support fish and fisheries in diverse tropical seascapes - Christopher J. Fulton; Charlotte Berkström; Shaun K. Wilson; Rene A. Abesamis; Michael Bradley; Carolina Åkerlund; Luke T. Barrett; Abner A. Bucol; Dinorah H. Chacin; Karen M. Chong‐Seng; Darren J. Coker; Martial Depczynski; et al. (Fish and Fisheries, 2020)
Canopy‐forming macroalgae can construct extensive meadow habitats in tropical seascapes occupied by fishes that span a diversity of taxa, life‐history stages and ecological roles. Our synthesis assessed whether these tropical macroalgal habitats have unique fish assemblages, provide fish nurseries and support local fisheries. We also applied a meta‐analysis of independent surveys across 23 tropical reef locations in 11 countries to examine how macroalgal canopy condition is related to the abundance of macroalgal‐associated fishes. Over 627 fish species were documented in tropical macroalgal meadows, with 218 of these taxa exhibiting higher local abundance within this habitat (cf. nearby coral reef) during at least one life‐history stage. Major overlap (40%–43%) in local fish species richness among macroalgal and seagrass or coral reef habitats suggest macroalgal meadows may provide an important habitat refuge. Moreover, the prominence of juvenile fishes suggests macroalgal meadows facilitate the triphasic life cycle of many fishes occupying diverse tropical seascapes. Correlations between macroalgal canopy structure and juvenile abundance suggests macroalgal habitat condition can influence levels of replenishment in tropical fish populations, including the majority of macroalgal‐associated fishes that are targeted by commercial, subsistence or recreational fisheries. While many macroalgal‐associated fishery species are of minor commercial value, their local importance for food and livelihood security can be substantial (e.g. up to 60% of landings in Kenyan reef fisheries). Given that macroalgal canopy condition can vary substantially with sea temperature, there is a high likelihood that climate change will impact macroalgal‐associated fish and fisheries.

Row-crop planter performance to support variable-rate seeding of maize - S. S. Virk; J. P. Fulton; W. M. Porter; G. L. Pate (Precision Agriculture, 2020)
Current planting technology possesses the ability to increase crop productivity and improve field efficiency by precisely metering and placing crop seeds. Planter performance depends on determining and utilizing optimal settings for different planting variables such as seed depth, down pressure, and seed metering unit. The evolution of “Big Data” in agriculture today brings focus on the need for quality as-planted and yield mapping data. Therefore, an investigation was conducted to evaluate the performance of current planting technology for accurate placement of seeds while understanding the accuracy of as-planted data. Two studies consisting of two different setups on a 6-row, John Deere planter for seeding of maize ( Zea mays L.) were conducted. The first study aimed at assessing planter performance at 2 depth settings (25 and 51 mm) and four different down pressure settings (varying from none to high), while the second study focused on evaluating planter performance during variable-rate seeding with treatments consisting of two seed metering units (John Deere Standard and Precision Planting’s eSet setups) with five different seeding rates and four ground speed treatments which provided a combination of 20 different meter speeds. Field data collection consisted of measuring plant emergence, plant population and seed depth whereas plant spacing, plant population after emergence along with distance and location for rate changes within the field were also recorded for the variable-rate seeding study. Results indicated that both depth setting and downforce affected final seeding depth. Measured seed depth was significantly different from the target depth even though time was spent adjusting the units to achieve the desired prior to planting. Crop emergence did not vary significantly for the different depth and downforce settings except for target depth in Field 1. Results from the variable-rate study indicated that seeding rate changes were accomplished within a quick response time (< 1 s) at all ground speeds regardless of magnitude of rate change. Data showed that planter performance in terms of emergence and plant spacing CV was comparable for most of the meter speeds (17.4–33.5 rpm) among the two seed meters utilized in the study. Plant spacing CV increased with an increase in meter speed, however no significant differences existed among meter speeds in the range of 17.4–33.5 rpm. Results implied that correct seed metering unit setup is very critical to obtain expected performance of today’s planting technology. A concerning find was that the quality of as-applied maps from the commercial variable-rate display was not reflective of the actual planter performance in the field. The study recommended that operators need to ensure the correct planter and display setups in order to achieve needed seed placement performance to support variable-rate seeding.

A role for leptin and ghrelin in the augmentation of heroin seeking induced by chronic food restriction - Tracey M. D’Cunha; Alexandra Chisholm; Cecile Hryhorczuk; Stephanie Fulton; Uri Shalev (Psychopharmacology, 2020)

Complete genome sequence of bovine herpesvirus type 1.1 (BoHV-1.1) Los Angeles (LA) strain and its genotypic relationship to BoHV-1.1 Cooper and more recently isolated wild-type field strains - Jean M. d’Offay; Robert W. Fulton; R. Eberle; Edward J. Dubovi; Christopher C. L. Chase (Archives of Virology, 2019)

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Current Status and Future Challenges of Weather Radar Polarimetry: Bridging the Gap between Radar Meteorology/Hydrology/Engineering and Numerical Weather Prediction - Guifu Zhang; Vivek N. Mahale; Bryan J. Putnam; Youcun Qi; Qing Cao; Andrew D. Byrd; Petar Bukovcic; Dusan S. Zrnic; Jidong Gao; Ming Xue; Youngsun Jung; Heather D. Reeves; et al. (Advances in Atmospheric Sciences, 2019)

Identifying important species that amplify or mitigate the interactive effects of human impacts on marine food webs - Gary P. Griffith; Peter G. Strutton; Jayson M. Semmens; Elizabeth A. Fulton (Conservation Biology, 2019)
Some species may have a larger role than others in the transfer of complex effects of multiple human stressors, such as changes in biomass, through marine food webs. We devised a novel approach to identify such species. We constructed annual interaction‐effect networks (IENs) of the simulated changes in biomass between species of the southeastern Australian marine system. Each annual IEN was composed of the species linked by either an additive (sum of the individual stressor response), synergistic (lower biomass compared with additive effects), or antagonistic (greater biomass compared with additive effects) response to the interaction effect of ocean warming, ocean acidification, and fisheries. Structurally, over the simulation period, the number of species and links in the synergistic IENs increased and the network structure became more stable. The stability of the antagonistic IENs decreased and became more vulnerable to the loss of species. In contrast, there was no change in the structural attributes of species linked by an additive response. Using indices common in food‐web and network theory, we identified the species in each IEN for which a change in biomass from stressor effects would disproportionately affect the biomass of other species via direct and indirect local, intermediate, and global predator–prey feeding interactions. Knowing the species that transfer the most synergistic or antagonistic responses in a food‐web may inform conservation under increasing multiple‐stressor impacts.

A Seasonally Dynamic Estuarine Ecosystem Provides a Diverse Prey Base for Elasmobranchs - Sharon L. Every; Christopher J. Fulton; Heidi R. Pethybridge; Peter M. Kyne; David A. Crook (Estuaries and Coasts, 2019)

Ecosystems say good management pays off - Elizabeth A. Fulton; André E. Punt; Catherine M. Dichmont; Chris J. Harvey; Rebecca Gorton (Fish and Fisheries, 2019)
Understanding the strengths and weaknesses of alternative assessment methods, harvest strategies and management approaches are an important part of operationalizing single‐species and ecosystem‐based fisheries management. Simulations run using two variants of a whole‐of‐ecosystem model for the Southern and Eastern Scalefish and Shark Fishery ( SESSF ) area shows that (a) data‐rich assessments outperform data‐poor assessments for target species and that this performance is reflected in the values of many system‐level ecosystem indicators; (b) ecosystem and multispecies management outperforms single‐species management applied over the same domain; (c) investment in robust science‐based fisheries management pays dividends even when there are multiple jurisdictions, some of which are not implementing effective management; and (d) that multispecies yield‐oriented strategies can deliver higher total catches without a notable decline in overall system performance, although the resulting system structure is different to that obtained with other forms of ecosystem‐based management.

Climate change alterations to ecosystem dominance: how might sponge‐dominated reefs function? - James J. Bell; Alberto Rovellini; Simon K. Davy; Michael W. Taylor; Elizabeth A. Fulton; Matthew R. Dunn; Holly M. Bennett; Nora M. Kandler; Heidi M. Luter; Nicole S. Webster (Ecology, 2018)
Anthropogenic stressors are impacting ecological systems across the world. Of particular concern are the recent rapid changes occurring in coral reef systems. With ongoing degradation from both local and global stressors, future reefs are likely to function differently from current coral‐dominated ecosystems. Determining key attributes of future reef states is critical to reliably predict outcomes for ecosystem service provision. Here we explore the impacts of changing sponge dominance on coral reefs. Qualitative modelling of reef futures suggests that changing sponge dominance due to increased sponge abundance will have different outcomes for other trophic levels compared with increased sponge dominance as a result of declining coral abundance. By exploring uncertainty in the model outcomes we identify the need to (1) quantify changes in carbon flow through sponges, (2) determine the importance of food limitation for sponges, (3) assess the ubiquity of the recently described “sponge loop,” (4) determine the competitive relationships between sponges and other benthic taxa, particularly algae, and (5) understand how changing dominance of other organisms alters trophic pathways and energy flows through ecosystems. Addressing these knowledge gaps will facilitate development of more complex models that assess functional attributes of sponge‐dominated reef ecosystems.

Fishery Development and Exploitation in South East Australia - Camilla Novaglio; Anthony D. M. Smith; Stewart Frusher; Francesco Ferretti; Neil Klaer; Elizabeth A. Fulton (Frontiers in Marine Science, 2018)

Comparative Toxicity of Two Chemical Dispersants and Dispersed Oil in Estuarine Organisms - M. E. DeLorenzo; P. B. Key; K. W. Chung; E. Pisarski; B. Shaddrix; E. F. Wirth; P. L. Pennington; J. Wade; M. Franco; M. H. Fulton (Archives of Environmental Contamination and Toxicology, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Climatic conditions and nursery habitat quality provide indicators of reef fish recruitment strength - Shaun K. Wilson; Martial Depczynski; Thomas H. Holmes; Mae M. Noble; Ben T. Radford; Paul Tinkler; Christopher J. Fulton (Limnology and Oceanography, 2017)
Identifying and protecting nursery habitats for species is a key conservation strategy for the long‐term sustainability of populations. In tropical ecosystems, macroalgal habitats have recently been identified as nurseries for fish of commercial and conservation significance. Here, we explore how local‐scale variations in seaweed habitat quality interact with large‐scale climatic conditions (Southern Oscillation Index, SOI) to influence the recruitment of three tropical fish species ( Lethrinus spp.), often targeted by fishers. New fish recruits and juveniles of all species were almost exclusively found in macroalgal nursery habitats, while adults of two of these species were predominantly found on adjacent coral reefs. Annual supply rates of new recruits were found to be strongly correlated to variations in the SOI, with La Nina conditions associated with higher recruitment. However, local rates of recruitment were generally poor predictors of older juvenile abundance. Instead, local juvenile abundance was more closely related to structural characteristics of macroalgae nursery habitat quality (density, canopy height, canopy cover) and/or predator biomass, at the time of survey, with species‐specific habitat associations apparent. Given the dynamic nature of fish recruitment supply to the SOI, coupled with the effects of climatic and oceanic processes on the structure of macroalgal patches, these results suggest protection of macroalgal nursery habitats that maintain high canopy density, height and cover is critical to supporting the conservation of fish populations.

Cyprinid herpesvirus 3 as a potential biological control agent for carp ( Cyprinus carpio ) in Australia: susceptibility of non‐target species - K A McColl; A Sunarto; J Slater; K Bell; M Asmus; W Fulton; K Hall; P Brown; D Gilligan; J Hoad; L M Williams; M St J Crane (Journal of Fish Diseases, 2017)
Carp ( Cyprinus carpio L.) is a pest species in Australian waterways, and cyprinid herpesvirus 3 (Cy HV ‐3) is being considered as a potential biological control (biocontrol) agent. An important consideration for any such agent is its target specificity. In this study, the susceptibility to Cy HV ‐3 of a range of non‐target species ( NTS ) was tested. The NTS were as follows: 13 native Australian, and one introduced, fish species; a lamprey species; a crustacean; two native amphibian species (tadpole and mature stages); two native reptilian species; chickens; and laboratory mice. Animals were exposed to 100–1000 times the approximate minimum amount of Cy HV ‐3 required to cause disease in carp by intraperitoneal and/or bath challenge, and then examined clinically each day over the course of 28 days post‐challenge. There were no clinical signs, mortalities or histological evidence consistent with a viral infection in a wide taxonomic range of NTS . Furthermore, there was no molecular evidence of infection with Cy HV ‐3, and, in particular, all RT ‐ PCR s for viral mRNA were negative. As a consequence, the results encourage further investigation of Cy HV ‐3 as a potential biocontrol agent that is specific for carp.

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Importance of soft canopy structure for labrid fish communities in estuarine mesohabitats - Joshua R. van Lier; David Harasti; Roger Laird; Mae M. Noble; Christopher J. Fulton (Marine Biology, 2017)

Ecosystem effects of invertebrate fisheries - Tyler D Eddy; Heike K Lotze; Elizabeth A Fulton; Marta Coll; Cameron H Ainsworth; Júlio Neves de Araújo; Catherine M Bulman; Alida Bundy; Villy Christensen; John C Field; Neil A Gribble; Mejs Hasan; et al. (Fish and Fisheries, 2017)
Since the 1950s, invertebrate fisheries catches have rapidly expanded globally to more than 10 million tonnes annually, with twice as many target species, and are now significant contributors to global seafood provision, export, trade and local livelihoods. Invertebrates play important and diverse functional roles in marine ecosystems, yet the ecosystem effects of their exploitation are poorly understood. Using 12 ecosystem models distributed worldwide, we analysed the trade‐offs of various invertebrate fisheries and their ecosystem effects as well as ecological indicators. Although less recognized for their contributions to marine food webs, our results show that the magnitude of trophic impacts of invertebrates on other species of commercial and conservation interest is comparable with those of forage fish. Generally, cephalopods showed the strongest ecosystem effects and were characterized by a strong top‐down predatory role. Lobster, and to a lesser extent, crabs, shrimp and prawns, also showed strong ecosystem effects, but at lower trophic levels. Benthic invertebrates, including epifauna and infauna, also showed considerable ecosystem effects, but with strong bottom‐up characteristics. In contrast, urchins, bivalves, and gastropods showed generally lower ecosystem effects in our simulations. Invertebrates also strongly contributed to benthic–pelagic coupling, with exploitation of benthic invertebrates impacting pelagic fishes and vice versa. Finally, on average, invertebrates produced maximum sustainable yield at lower levels of depletion (~45%) than forage fish (~65%), highlighting the need for management targets that avoid negative consequences for target species and marine ecosystems as a whole.

A role for histone acetylation mechanisms in adolescent alcohol exposure-induced deficits in hippocampal brain-derived neurotrophic factor expression and neurogenesis markers in adulthood - Amul J. Sakharkar; Ryan P. Vetreno; Huaibo Zhang; Dadasaheb M. Kokare; Fulton T. Crews; Subhash C. Pandey (Brain Structure and Function, 2016)

Complete genomic sequence and comparative analysis of four genital and respiratory isolates of bovine herpesvirus subtype 1.2b (BoHV-1.2b), including the prototype virus strain K22 - Jean M. d’Offay; R. Eberle; Robert W. Fulton; Peter D. Kirkland (Archives of Virology, 2016)

Is risk consistent across tier‐based harvest control rule management systems? A comparison of four case‐studies - Catherine M Dichmont; André E Punt; Natalie Dowling; José A A De Oliveira; Lorne R Little; Miriana Sporcic; Elizabeth Fulton; Rebecca Gorton; Neil Klaer; Malcolm Haddon; David C Smith (Fish and Fisheries, 2016)
There can be substantial differences in data quality and quantity among fished species. Consequently, the quality and type of assessments can also vary substantially. However, all species, especially those that are targeted, need to be managed. Several jurisdictions have developed hierarchical tier systems that categorize stocks based on, for example, the data available for assessment purposes and/or the extent to which quantities on which management advice is based can be estimated. Four case‐studies (Australia's Southern and Eastern Scalefish and Shark Fishery, the USA west coast groundfishery, the USA Alaskan crab fishery and EU fisheries) are used to contrast the types of hierarchical tier systems available, and to assess the extent to which each system constrains risk to be equivalent among the tiers (termed risk equivalency). Only the Australian system explicitly aims to achieve risk equivalency. However, this intent has not been fully operationalized. Our review reveals that best practice is not to define tiers simply on data availability, but also on what the assessments based on those data are capable of estimating. In addition, clearly differentiating the quantification of uncertainty from how decision‐makers wish to address that uncertainty would simplify justification of buffers (the gap between the assessment‐produced target catch or effort and the final management decision that accounts for uncertainty and risk). Risk equivalency can be achieved using management strategy evaluation to select the values for control variables, which determine the buffer given the uncertainty associated with the assessment.

Climate‐driven changes to ocean circulation and their inferred impacts on marine dispersal patterns - Laura J. Wilson; Christopher J. Fulton; Andrew McC Hogg; Karen E. Joyce; Ben T. M. Radford; Ceridwen I. Fraser (Global Ecology and Biogeography, 2016)
Aim The dispersal and distribution patterns of many marine organisms are driven by oceanographic conditions, which are influenced by global climate. Climate‐driven oceanographic changes are thus likely to result in biogeographical changes. We assess how recent and predicted oceanographic changes affect the dispersal capacities and distributions of ecologically important (especially habitat‐forming) marine organisms. Location We include studies from tropical, temperate and sub‐polar regions to draw globally relevant conclusions. Methods We review biogeographical, biological and oceanographic studies to critically evaluate emerging trends in biogeographical responses to climate‐driven oceanographic changes, and predict how future changes will affect marine ecosystems. Results Many oceanic dispersal pathways are being altered by climate change. These changes will affect marine ecosystems by differentially affecting the replenishment potential and connectivity of key habitat‐forming species. In particular, the length of propagule pre‐competency periods, propagule behaviour and the geographical distance between areas of suitable habitat will be critical in determining how oceanographic changes affect the pattern and success of dispersal events, including the likelihood of species experiencing poleward range shifts in response to a warming climate. Main conclusions Future climate‐driven oceanographic changes are likely to strengthen or weaken different oceanic dispersal pathways, which will either increase or decrease the potential for dispersal and connectivity in various marine taxa according to the interaction between the local oceanographic, geographical and taxon‐specific biological factors. A key focus for future work should be the development of fine‐scale near‐shore ocean circulation models that can be used to assess the dispersal response of key marine taxa under various marine climate change scenarios.

Planning adaptation to climate change in fast-warming marine regions with seafood-dependent coastal communities - Alistair J. Hobday; Kevern Cochrane; Nicola Downey-Breedt; James Howard; Shankar Aswani; Val Byfield; Greg Duggan; Elethu Duna; Leo X. C. Dutra; Stewart D. Frusher; Elizabeth A. Fulton; Louise Gammage; et al. (Reviews in Fish Biology and Fisheries, 2016)

Species traits and climate velocity explain geographic range shifts in an ocean‐warming hotspot - Jennifer M. Sunday; Gretta T. Pecl; Stewart Frusher; Alistair J. Hobday; Nicole Hill; Neil J. Holbrook; Graham J. Edgar; Rick Stuart‐Smith; Neville Barrett; Thomas Wernberg; Reg A. Watson; Dan A. Smale; et al. (Ecology Letters, 2015)
Species' ranges are shifting globally in response to climate warming, with substantial variability among taxa, even within regions. Relationships between range dynamics and intrinsic species traits may be particularly apparent in the ocean, where temperature more directly shapes species' distributions. Here, we test for a role of species traits and climate velocity in driving range extensions in the ocean‐warming hotspot of southeast Australia. Climate velocity explained some variation in range shifts, however, including species traits more than doubled the variation explained. Swimming ability, omnivory and latitudinal range size all had positive relationships with range extension rate, supporting hypotheses that increased dispersal capacity and ecological generalism promote extensions. We find independent support for the hypothesis that species with narrow latitudinal ranges are limited by factors other than climate. Our findings suggest that small‐ranging species are in double jeopardy, with limited ability to escape warming and greater intrinsic vulnerability to stochastic disturbances.

Modelling dynamic ecosystems: venturing beyond boundaries with the Ecopath approach - M. Coll; E. Akoglu; F. Arreguín-Sánchez; E. A. Fulton; D. Gascuel; J. J. Heymans; S. Libralato; S. Mackinson; I. Palomera; C. Piroddi; L. J. Shannon; J. Steenbeek; et al. (Reviews in Fish Biology and Fisheries, 2015)

Distribution and sources of PCBs (Aroclor 1268) in the Sapelo Island National Estuarine Research Reserve - E. F. Wirth; P. L. Pennington; C. Cooksey; L. Schwacke; L. Balthis; J. Hyland; M. H. Fulton (Environmental Monitoring and Assessment, 2014)

Seasonal changes in habitat structure underpin shifts in macroalgae-associated tropical fish communities - S. K. Wilson; C. J. Fulton; M. Depczynski; T. H. Holmes; M. M. Noble; B. Radford; P. Tinkler (Marine Biology, 2014)

Impacts of Mountaintop Removal and Valley Fill Coal Mining on C and N Processing in Terrestrial Soils and Headwater Streams - Roger A. Burke; Ken M. Fritz; Chris D. Barton; Brent R. Johnson; Stephanie Fulton; Dean Hardy; David A. Word; Jeff D. Jack (Water, Air, & Soil Pollution, 2014)

Relationship between land use classification and grass shrimp Palaemonetes spp. population metrics in coastal watersheds - James W. Daugomah; P. B. Key; J. B. West; N. R. Shea; S. McDaniel; P. L. Pennington; M. H. Fulton (Environmental Monitoring and Assessment, 2014)

Foraging in corallivorous butterflyfish varies with wave exposure - Mae M. Noble; Morgan S. Pratchett; Darren J. Coker; Christopher Cvitanovic; Christopher J. Fulton (Coral Reefs, 2014)

Novel molecular determinants of viral susceptibility and resistance in the lipidome of E miliania huxleyi - James M. Fulton; Helen F. Fredricks; Kay D. Bidle; Assaf Vardi; B. Jacob Kendrick; Giacomo R. DiTullio; Benjamin A. S. Van Mooy (Environmental Microbiology, 2014)
Summary Viruses play a key role in controlling the population dynamics of algae, including E miliania huxleyi , a globally distributed haptophyte with calcite coccoliths that comprise ca. 50% of the sinking carbonate flux from the surface ocean. E miliania huxleyi viruses ( EhVs ) routinely infect and terminate E . huxleyi blooms. EhVs are surrounded by a lipid envelope, which we found to be comprised largely of glycosphingolipids ( GSLs ) with lesser amounts of polar glycerolipids. Infection appears to involve membrane fusion between the virus and host, and we hypothesized that specific polar lipids may facilitate virus attachment. We identified three novel intact polar lipids in E . huxleyi strain CCMP 374 and EhV 86, including a GSL with a monosaccharide sialic acid headgroup ( sGSL ); for all 11 E . huxleyi strains we tested, there was a direct relationship between sGSL content and sensitivity to infection by EhV 1, EhV 86 and EhV 163. In mesocosms, the E . huxleyi population with greatest initial sGSL content had the highest rate of virus‐induced mortality. We propose potential physiological roles for sGSL that would be beneficial for growth but leave cells susceptible to infection, thus furthering the discussion of R ed Q ueen‐based co‐evolution and the cost(s) of sensitivity and resistance in the dynamic E . huxleyi ‐ EhV system.

Isolation and characterization of lipid rafts in E miliania huxleyi : a role for membrane microdomains in host–virus interactions - Suzanne L. Rose; James M. Fulton; Christopher M. Brown; Frank Natale; Benjamin A. S. Van Mooy; Kay D. Bidle (Environmental Microbiology, 2014)
Summary Coccolithoviruses employ a suite of glycosphingolipids ( GSLs ) to successfully infect the globally important coccolithophore E miliania huxleyi . Lipid rafts, chemically distinct membrane lipid microdomains that are enriched in GSLs and are involved in sensing extracellular stimuli and activating signalling cascades through protein–protein interactions, likely play a fundamental role in host–virus interactions. Using combined lipidomics, proteomics and bioinformatics, we isolated and characterized the lipid and protein content of lipid rafts from control E . huxleyi cells and those infected with EhV 86, the type strain for C occolithovirus . Lipid raft‐enriched fractions were isolated and purified as buoyant, detergent‐resistant membranes ( DRMs ) in OptiPrep density gradients. Transmission electron microscopy of vesicle morphology, polymerase chain reaction amplification of the EhV major capsid protein gene and immunoreactivity to flotillin antisera served as respective physical, molecular and biochemical markers. Subsequent lipid characterization of DRMs via high performance liquid chromatography‐triple quadrapole mass spectrometry revealed four distinct GSL classes. Parallel proteomic analysis confirmed flotillin as a major lipid raft protein, along with a variety of proteins affiliated with host defence, programmed cell death and innate immunity pathways. The detection of an EhV 86‐encoded C ‐type lectin‐containing protein confirmed that infection occurs at the interface between lipid rafts and cellular stress/death pathways via specific GSLs and raft‐associated proteins.

Multispecies fisheries management and conservation: tactical applications using models of intermediate complexity - Éva E Plagányi; André E Punt; Richard Hillary; Elisabetta B Morello; Olivier Thébaud; Trevor Hutton; Richard D Pillans; James T Thorson; Elizabeth A Fulton; Anthony D M Smith; Franz Smith; Peter Bayliss; et al. (Fish and Fisheries, 2014)
Stakeholders increasingly expect ecosystem assessments as part of advice on fisheries management. Quantitative models to support fisheries decision‐making may be either strategic (‘big picture’, direction‐setting and contextual) or tactical (focused on management actions on short timescales), with some strategic models informing the development of tactical models. We describe and review ‘ M odels of I ntermediate C omplexity for E cosystem assessments’ ( MICE ) that have a tactical focus, including use as ecosystem assessment tools. MICE are context‐ and question‐driven and limit complexity by restricting the focus to those components of the ecosystem needed to address the main effects of the management question under consideration. Stakeholder participation and dialogue is an integral part of this process. MICE estimate parameters through fitting to data, use statistical diagnostic tools to evaluate model performance and account for a broad range of uncertainties. These models therefore address many of the impediments to greater use of ecosystem models in strategic and particularly tactical decision‐making for marine resource management and conservation. MICE are capable of producing outputs that could be used for tactical decision‐making, but our summary of existing models suggests this has not occurred in any meaningful way to date. We use a model of the pelagic ecosystem in the C oral S ea and a linked catchment and ocean model of the G ulf of C arpentaria, A ustralia, to illustrate how MICE can be constructed. We summarize the major advantages of the approach, indicate opportunities for the development of further applications and identify the major challenges to broad adoption of the approach.

Sea temperature shapes seasonal fluctuations in seaweed biomass within the Ningaloo coral reef ecosystem - Christopher J. Fulton; Martial. Depczynski; Thomas H. Holmes; Mae M. Noble; Ben Radford; Thomas Wernberg; Shaun K. Wilson (Limnology and Oceanography, 2014)
Environmental drivers of seaweed biomass were investigated at Ningaloo, Western Australia, a coral reef ecosystem with negligible anthropogenic influences on seaweeds from fishing, farming, or eutrophication. Periodic surveys of benthic macroalgae occupying seaweed‐dominated beds within the lagoon at two locations (Coral Bay, Tantabiddi) were made during winter, spring, and late summer over a 26 month period. Canopy‐forming Sargassum spp. biomass fluctuated over a seasonal growth—decay cycle, with highest values in the warm summer months (up to 1013 g fresh weight 0.25 m −2 at Coral Bay) and lowest values in winter (down to 155 g fresh weight 0.25 m −2 at Tantabiddi). Conversely, prominent understory seaweed genera Dictyopteris and Lobophora reached peak biomass in winter, when the Sargassum spp. canopy was lowest. Sargassum spp. biomass variation could be attributed largely to time (52%), location (21%), and site (26%), with low variation within individual seaweed beds (1%). Statistical analysis of the influence of five environmental variables (temperature, light, wind‐driven upwelling, rainfall, significant wave height) indicated that location and sea temperature (1 month antecedent to biomass) provided the best explanation for Sargassum spp. biomass fluctuations. While sea temperature is a key driver of seaweed temporal dynamics, heterogeneity at the kilometer scale suggests that spatial context is also important. Given the important role of seaweeds in many ecosystem processes, this strong biophysical coupling between Sargassum spp. biomass and sea temperature suggests that thermal climate change will significantly affect coral reef productivity and biodiversity.

Assessment of animal impacts on bacterial water quality in a South Carolina, USA tidal creek system - L. F. Webster; D. A. Graves; D. A. Eargle; D. E. Chestnut; J. A. Gooch; M. H. Fulton (Environmental Monitoring and Assessment, 2013)

Complete genome sequence of the NVSL BoHV-1.1 Cooper reference strain - Jean M. d’Offay; Robert W. Fulton; R. Eberle (Archives of Virology, 2013)

Invertebrate Community Patterns in Seasonal Ponds in Minnesota, USA: Response to Hydrologic and Environmental Variability - Matthew M. Bischof; Mark A. Hanson; Mark R. Fulton; Randy K. Kolka; Stephen D. Sebestyen; Malcolm G. Butler (Wetlands, 2013)

Phenotypic stability of Pro347Leu rhodopsin transgenic pigs as indicated by photoreceptor cell degeneration - Jeffrey R. Sommer; Fulton Wong; Robert M. Petters (Transgenic Research, 2011)

Using sprint swimming performance to predict upstream passage of the endangered Macquarie perch in a highly regulated river - D. STARRS; B. C. EBNER; M. LINTERMANS; C. J. FULTON (Fisheries Management and Ecology, 2011)
Barriers to migration are a major threat to freshwater fish populations. A novel measurement of swimming speed performance and an analytical model were used to calculate the probability that endangered Macquarie perch, Macquaria australasica Cuvier, can swim through instream structures. Over the range of river discharges (2.7–166 ML day −1 ) and temperatures (10–22 °C) examined, M. australasica could successfully pass through a rock‐ramp fishway and nearby natural riffles under most river discharges, whilst pipe culverts were passable only to large individuals (>17.7 cm total length) under a high river discharge. Cold water temperatures (below 16 °C) significantly reduced the likelihood of passage in each case. It was concluded that both the volume and thermal characteristics of environmental flow releases should be considered when assessing and remediating potential instream barriers to fish passage in regulated river systems.

Lessons in modelling and management of marine ecosystems: the Atlantis experience - Elizabeth A Fulton; Jason S Link; Isaac C Kaplan; Marie Savina‐Rolland; Penelope Johnson; Cameron Ainsworth; Peter Horne; Rebecca Gorton; Robert J Gamble; Anthony D M Smith; David C Smith (Fish and Fisheries, 2011)
Models are key tools for integrating a wide range of system information in a common framework. Attempts to model exploited marine ecosystems can increase understanding of system dynamics; identify major processes, drivers and responses; highlight major gaps in knowledge; and provide a mechanism to ‘road test’ management strategies before implementing them in reality. The Atlantis modelling framework has been used in these roles for a decade and is regularly being modified and applied to new questions (e.g. it is being coupled to climate, biophysical and economic models to help consider climate change impacts, monitoring schemes and multiple use management). This study describes some common lessons learned from its implementation, particularly in regard to when these tools are most effective and the likely form of best practices for ecosystem‐based management (EBM). Most importantly, it highlighted that no single management lever is sufficient to address the many trade‐offs associated with EBM and that the mix of measures needed to successfully implement EBM will differ between systems and will change through time. Although it is doubtful that any single management action will be based solely on Atlantis, this modelling approach continues to provide important insights for managers when making natural resource management decisions.

Human behaviour: the key source of uncertainty in fisheries management - Elizabeth A Fulton; Anthony D M Smith; David C Smith; Ingrid E van Putten (Fish and Fisheries, 2011)
There is broad consensus that the main problem facing fisheries globally is too many boats chasing too few fish. Unfortunately it is also possible to argue that there are too many proposed solutions and not enough practical answers to improving fisheries management. There is a deepening divide between those who propose alternative regulatory controls on fishers, including establishing large areas permanently closed to fishing, and those who argue for better alignment of incentives combined with broad participation of resource users in fishery management decisions (in simple terms, between top down and bottom up systems of governance). However despite the choice of policy instruments used, a consistent outcome is that resource users behave in a manner that is often unintended by the designers of the management system. Hence whilst uncertainty is broadly recognized as a pervasive feature of fisheries management, to date most of the attention has focussed on only part of that uncertainty – scientific uncertainty about the status of exploited resources. The effect of uncertainty generated on the human side of fisheries science and management has received much less attention. However, the uncertainty generated by unexpected resource user behaviour is critical as it has unplanned consequences and leads to unintended management outcomes. Using empirical evidence of unexpected resource user behaviour and reviewing current responses to unexpected management outcomes, we identify different approaches that both improve prediction of human behaviour in fisheries systems and identify management measures that are more robust to these sources of uncertainty. However, unless the micro scale drivers of human behaviour that contribute to macro scale implementation uncertainty are communicated effectively to managers and considered more regularly and in greater depth, unanticipated responses to management actions will continue to undermine management systems and threaten the sustainability of fisheries.

Effects of climate‐driven primary production change on marine food webs: implications for fisheries and conservation - C. J. BROWN; E. A. FULTON; A. J. HOBDAY; R. J. MATEAR; H. P. POSSINGHAM; C. BULMAN; V. CHRISTENSEN; R. E. FORREST; P. C. GEHRKE; N. A. GRIBBLE; S. P. GRIFFITHS; H. LOZANO‐MONTES; et al. (Global Change Biology, 2010)
Climate change is altering the rate and distribution of primary production in the world's oceans. Primary production is critical to maintaining biodiversity and supporting fishery catches, but predicting the response of populations to primary production change is complicated by predation and competition interactions. We simulated the effects of change in primary production on diverse marine ecosystems across a wide latitudinal range in Australia using the marine food web model Ecosim. We link models of primary production of lower trophic levels (phytoplankton and benthic producers) under climate change with Ecosim to predict changes in fishery catch, fishery value, biomass of animals of conservation interest, and indicators of community composition. Under a plausible climate change scenario, primary production will increase around Australia and generally this benefits fisheries catch and value and leads to increased biomass of threatened marine animals such as turtles and sharks. However, community composition is not strongly affected. Sensitivity analyses indicate overall positive linear responses of functional groups to primary production change. Responses are robust to the ecosystem type and the complexity of the model used. However, model formulations with more complex predation and competition interactions can reverse the expected responses for some species, resulting in catch declines for some fished species and localized declines of turtle and marine mammal populations under primary productivity increases. We conclude that climate‐driven primary production change needs to be considered by marine ecosystem managers and more specifically, that production increases can simultaneously benefit fisheries and conservation. Greater focus on incorporating predation and competition interactions into models will significantly improve the ability to identify species and industries most at risk from climate change.

Effects of chemically spiked sediments on estuarine benthic communities: a controlled mesocosm study - W. L. Balthis; J. L. Hyland; M. H. Fulton; P. L. Pennington; C. Cooksey; P. B. Key; M. E. DeLorenzo; E. F. Wirth (Environmental Monitoring and Assessment, 2010)

Effects of the antifouling compound, Irgarol 1051, on a simulated estuarine salt marsh ecosystem - M. E. DeLorenzo; P. L. Pennington; K. W. Chung; M. C. Finnegan; M. H. Fulton (Ecotoxicology, 2009)

Atropine treatment modifies LPS-induced inflammatory response and increases survival - J. M. Fuentes; W. B. Fulton; D. Nino; M. A. Talamini; A. De. Maio (Inflammation Research, 2008)

Applying new tools to cephalopod trophic dynamics and ecology: perspectives from the Southern Ocean Cephalopod Workshop, February 2–3, 2006 - G. D. Jackson; P. Bustamante; Y. Cherel; E. A. Fulton; E. P. M. Grist; C. H. Jackson; P. D. Nichols; H. Pethybridge; K. Phillips; R. D. Ward; J. C. Xavier (Reviews in Fish Biology and Fisheries, 2007)

Dissecting quantitative trait variation—examples from the tomato - Steven D. Tanksley; Theresa M. Fulton (Euphytica, 2007)

Panmictic population structure in the hooded seal ( Cystophora cristata ) - D. W. COLTMAN; G. STENSON; M. O. HAMMILL; T. HAUG; C. S. DAVIS; T. L. FULTON (Molecular Ecology, 2007)
Two putative populations of hooded seals ( Cystophora cristata ) occur in the North Atlantic. The Greenland Sea population pup and breed on the pack ice near Jan Mayen (‘West Ice’) while the Northwest Atlantic population is thought to pup in the Davis Strait, in the Gulf of St. Lawrence (the ‘Gulf’), and off southern Labrador or northeast Newfoundland (the ‘Front’). We used microsatellite profiling of 300 individuals at 13 loci and mitochondrial DNA sequencing of the control region of 123 individuals to test for genetic differentiation between these four breeding herds. We found no significant genetic differences between breeding areas, nor evidence for cryptic nor higher level genetic structure in this species. The Greenland Sea breeding herd was genetically most distant from the Northwest Atlantic breeding areas; however, the differences were statistically nonsignificant. Our data therefore suggest that the world's hooded seals comprise a single panmictic genetic population.

An evaluation of contaminated estuarine sites using sediment quality guidelines and ecological assessment methodologies - M. Fulton; P. Key; E. Wirth; A. K. Leight; J. Daugomah; D. Bearden; S. Sivertsen; G. Scott (Ecotoxicology, 2006)

Molecular genotype identification of the Gallus gallus major histocompatibility complex - Janet E. Fulton; Helle R. Juul-Madsen; Christopher M. Ashwell; Amy M. McCarron; James A. Arthur; Neil P. O’Sullivan; Robert L. Taylor (Immunogenetics, 2006)

An Evaluation of Polycyclic Aromatic Hydrocarbon (PAH) Runoff from Highways Into Estuarine Wetlands of South Carolina - R. F. Van Dolah; G. H. M. Riekerk; M. V. Levisen; G. I. Scott; M. H. Fulton; D. Bearden; S. Sivertsen; K. W. Chung; D. M. Sanger (Archives of Environmental Contamination and Toxicology, 2005)

Surface Water Pesticide Movement from the Dade County Agricultural Area to the Everglades and Florida Bay via the C-111 Canal - M. H. Fulton; G. I. Scott; M. E. DeLorenzo; P. B. Key; D. W. Bearden; E. D. Strozier; C. J. Madden (Bulletin of Environmental Contamination and Toxicology, 2004)

Changes in fulvic acid redox state through the oxycline of a permanently ice-covered Antarctic lake - Jennifer R. Fulton; Diane M. McKnight; Rose M. Cory; Colin Stedmon; Elisabeth Blunt; Christine M. Foreman (Aquatic Sciences, 2004)

Advanced backcross QTL analysis of a Lycopersicon esculentum × L. pennellii cross and identification of possible orthologs in the Solanaceae - A. Frary; T. M. Fulton; D. Zamir; S. D. Tanksley (Theoretical and Applied Genetics, 2004)

The SLC4 family of HCO3 ? transporters - Michael F. Romero; Christiaan M. Fulton; Walter F. Boron (Pflügers Archiv - European Journal of Physiology, 2004)

Acetylcholinesterase Activity in Grass Shrimp and Aqueous Pesticide Levels from South Florida Drainage Canals - P. B. Key; M. H. Fulton; J. A. Harman-Fetcho; L. L. McConnell (Archives of Environmental Contamination and Toxicology, 2003)

Effects of Fipronil and Chlorpyrifos on Endocrine-Related Endpoints in Female Grass Shrimp (Palaemonetes pugio) - D. C. Volz; E. F. Wirth; M. H. Fulton; G. I. Scott; E. Strozier; D. S. Block; J. L. Ferry; S. S. Walse; G. T. Chandler (Bulletin of Environmental Contamination and Toxicology, 2003)

Toxicity of the Insecticides Fipronil and Endosulfan to Selected Life Stages of the Grass Shrimp ( Palaemonetes pugio ) - P. B. Key; K. W. Chung; A. D. Opatkiewicz; E. F. Wirth; M. H. Fulton (Bulletin of Environmental Contamination and Toxicology, 2003)

Baculovirus expression and antigenic characterization of the capsid proteins of three Norwalk-like viruses - X. Jiang; W. M. Zhong; T. Farkas; P. W. Huang; N. Wilton; E. Barrett; D. Fulton; R. Morrow; D. O. Matson (Archives of Virology, 2002)

Advanced backcross QTL analysis of a Lycopersicon esculentum ×Lycopersicon parviflorum cross - T. M. Fulton; S. Grandillo; T. Beck-Bunn; E. Fridman; A. Frampton; J. Lopez; V. Petiard; J. Uhlig; D. Zamir; S. D. Tanksley (Theoretical and Applied Genetics, 2000)

Toxicity of DDT to the Different Life Stages of the Mummichog Fundulus heteroclitus (Wabum) - D. I. Anadu; G. I. Scott; M. H. Fulton (Bulletin of Environmental Contamination and Toxicology, 1999)

The fit-1 common integration locus in human and mouse is closely linked to MYB - N.I. Barr; M. Stewart; C. Tsatsanis; R. Fulton; M. Hu; H. Tsujimoto; J.C. Neil (Mammalian Genome, 1999)

Toxicity of Sediment Associated PAHs to the Estuarine Crustaceans, Palaemonetes pugio and Amphiascus tenuiremis - E. F. Wirth *, M. H. Fulton; G. T. Chandler; P. B. Key; G. I. Scott (Bulletin of Environmental Contamination and Toxicology, 1998)

Azinphosmethyl Exposure to Grass Shrimp ( Palaemonetes pugio ) Life Stages with Emphasis on Larval Acetylcholinesterase Activity - P. B. Key; M. H. Fulton; S. L. Layman; G. I. Scott (Bulletin of Environmental Contamination and Toxicology, 1998)

Transport, degradation and cell wall-integration of XXFGol, a growth-regulating nonasaccharide of xyloglucan, in pea stems - Hildegard M. Warneck; Daniel C. Fulton; Hanns Ulrich Seitz; Stephen C. Fry (Planta, 1997)

Introgression and DNA marker analysis of Lycopersicon peruvianum, a wild relative of the cultivated tomato, into Lycopersicon esculentum, followed through three successive backcross generations - T. M. Fulton; J. C. Nelson; S. D. Tanksley (Theoretical and Applied Genetics, 1997)

QTL analysis of an advanced backcross of Lycopersicon peruvianum to the cultivated tomato and comparisons with QTLs found in other wild species - T. M. Fulton; T. Beck-Bunn; D. Emmatty; Y. Eshed; J. Lopez; V. Petiard; J. Uhlig; D. Zamir; S. D. Tanksley (Theoretical and Applied Genetics, 1997)

In Situ Monitoring of Dredged Material Spoil Sites Using the Oyster Crassostrea virginica - E. F. Wirth; G. I. Scott; M. H. Fulton; R. F. Van Dolah, P. P. Maier, N. Hadle; P. B. Key (Archives of Environmental Contamination and Toxicology, 1996)

In situ monitoring of dredged material spoil sites using the oyster Crassostrea virginica - E. F. Wirth; G. I. Scott; M. H. Fulton; R. F. Van Dolah; P. P. Maier; N. Hadley; J. W. Daugomah; P. B. Key (Archives of Environmental Contamination and Toxicology, 1996)

Cumulative effects of supplemental irrigation on fertilizer requirement, yield and dry matter content of early potatoes - J. M. Fulton; W. I. Findlay (American Journal of Potato Research, 1964)